Fetal Membrane Epigenetics - Zakar, Tamas; Paul, Jonathan W. (Frontiers in Physiology, 2020)
The characteristics of fetal membrane cells and their phenotypic adaptations to support pregnancy or promote parturition are defined by global patterns of gene expression controlled by chromatin structure. Heritable epigenetic chromatin modifications that include DNA methylation and covalent histone modifications establish chromatin regions permissive or exclusive of regulatory interactions defining the cell-specific scope and potential of gene activity. Non-coding RNAs acting at the transcriptional and post-transcriptional levels complement the system by robustly stabilizing gene expression patterns and contributing to ordered phenotype transitions. Here we review currently available information about epigenetic gene regulation in the amnion and the chorion laeve. In addition, we provide an overview of epigenetic phenomena in the decidua, which is the maternal tissue fused to the chorion membrane forming the anatomical and functional unit called choriodecidua. The relationship of gene expression with DNA (CpG) methylation, histone acetylation and methylation, micro RNAs, long non-coding RNAs and chromatin accessibility is discussed in the context of normal pregnancy, parturition and pregnancy complications. Data generated using clinical samples and cell culture models strongly suggests that epigenetic events are associated with the phenotypic transitions of fetal membrane cells during the establishment, maintenance and termination of pregnancy potentially driving and consolidating the changes as pregnancy progresses. Disease conditions and environmental factors may produce epigenetic footprints that indicate exposures and mediate adverse pregnancy outcomes. Although knowledge is expanding rapidly, fetal membrane epigenetics is still in an early stage of development necessitating further research to realize its remarkable basic and translational potential.